A technique to dry mount Hymenoptera (Hexapoda) from alcohol in a few seconds, and its application to other insect orders - Aguiar, Alexandre Pires (Zootaxa, 2012)
A new technique is presented that allows mounting insects directly from alcohol storage, while still wet or soaked, withoutany chemical treatment. It works particularly well for many groups of Hymenoptera, but not with delicate or softspecimens. Preliminary results are also commented for some Coleoptera, Diptera, Hemiptera, Mantodea, Neuroptera, andOrthoptera. External drying is performed with the aid of a small electric air pump. A 600 L/min air current quickly andefficiently spreads the specimen’s wings and pilosity, while helping to position the antennae, legs, and abdomen.Specimens need to be pinned, even if small and pinned with minutens; this generally means the new technique will workfor any insect greater than 3 mm long. This is precisely the size range for which an efficient mounting aid for alcohol preserved specimens was lacking.